Sudah Sampai Manakah Riset Keuangan Mikro Syariah Kita? - Aam S. Rusydiana (JURNAL EKONOMI DAN PERBANKAN SYARIAH, 2018)
This study tries to review the research around Islamic microfinance institution. It uses descriptive statistical analysis based on selected 100 journal publications or paper related to Islamic microfinance institution, both national and international journal. The entire sample journal publications have published for ten years from 2007 to 2016. The Results show that Islamic microfinance institute research is still dominated by the discussion about Islamic microfinance institution (54%), followed by eradication of poverty (25%), then financing the poor societies (11%) and the last is about management of Islamic microfinance institution (10%). In addition, Indonesia, Malaysia and Pakistan are being the highest of Islamic microfinance study area, while the majority of publications area are from Indonesia, United States and United Kingdom. Furthermore, the comparison of quantitative research and mixed methods are still less than the qualitative approach.